Culturally Responsive Teaching dan Relevansinya dengan Konsep IPA dalam Budaya Jawa Barat: Systematic Literature Review Menggunakan PRISMA - Rusyati, Lilit; Agustin, Rika Rafikah; Sriwulan, Wiwin; Hakim, Mohammad Ikhsanul (STKIP PGRI Bandar Lampung, 2025)
In order to accommodate students' varied cultural backgrounds and improve their educational experiences, culturally responsive teaching, or CRT, must be incorporated into science instruction. This study used a Systematic Literature Review (SLR) as its research method, following the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) standards. In order to investigate the connection between science concepts and West Java culture, this process entails “identification, screening, and included” of pertinent literature. It follows methodical and open procedures to guarantee the validity and reliability of the results. The findings of the analysis show that seventh, eighth, and ninth graders' science concepts are strongly tied to West Java cultural elements, such as traditional musical instruments, traditional sports, traditional foods, traditional dances, folk entertainment, and agricultural practices. This integration of local culture into the science curriculum enhances students' understanding and respect of their heritage while also making the learning environment more engaging.